Baiga Settlements in the Environs of Maikal Range of Central India - Prasad, Janki; Yadava, R. S. (National Geographical Journal of India, 2022)
Baiga is one of the particular vulnerable tribe groups in India which generally inhabits in hilly and forested tracts of central highlands of the country such as ranges of Maikal and Satpura. It is argued that the remote and inaccessible areas are occupied by the Baigas which is attributed to their security concerns from the interactions by the other societies. Their simple ways of life and nature loving personal traits reflect harmonious relationship of Baiga tribe with natural environment. Various spheres of their life are intimately associated with the forests and forest products. The study reveals that Baiga settlements are somewhat different from rest settlements of region in terms of its location, morphology and housing structure. In this study an attempt has been made to explore the relationships between natural environment and tribal society. Focus has been led to analysis of socio-cultural processes that shape and alter cultural landscape in a unique and specific manner. The study will be useful for the researchers interested in settlement geography as well as the scholars of social, cultural and environmental studies.